2015
DOI: 10.1167/iovs.14-16327
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of Corneal Phase Retardation Measurements by Polarization-Sensitive Optical Coherence Tomography

Abstract: Polarization-sensitive OCT showed good repeatability for phase retardation measurements of central corneas not only for normal corneas, but also for various diseased corneas. Polarization-sensitive OCT might be useful for evaluating corneal phase retardation, which is one of the parameters that defines birefringence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Fukuda et al showed that PS-OCT has high sensitivity to detect the keratoconus and is useful for grading the disease based on systematic clinical studies [92]. PS-OCT is a promising tool for screening and treatment control of keratoconus and also other corneal diseases [93].…”
Section: Anterior Eye Segment Imagingmentioning
confidence: 99%
“…Fukuda et al showed that PS-OCT has high sensitivity to detect the keratoconus and is useful for grading the disease based on systematic clinical studies [92]. PS-OCT is a promising tool for screening and treatment control of keratoconus and also other corneal diseases [93].…”
Section: Anterior Eye Segment Imagingmentioning
confidence: 99%
“…Because it is easy to detect both the anterior and posterior corneal surfaces, we quantitatively evaluated corneal phase retardation using an en face phase retardation map. 20,21 In that study, the phase retardation measured at the posterior surface of the cornea, which accumulates from the anterior to posterior surfaces, was analyzed in an en face manner. However, it is challenging to obtain an en face phase retardation map of a bleb.…”
mentioning
confidence: 99%
“…In our previous cornea study using PS-OCT, we have investigated phase retardation of cornea on en face images. In the case of cornea, it was easy to automatically mark the boundaries between air and cornea/cornea and anterior chamber 35 , 36 . However, in the case of blebs, sometimes it is difficult to establish a clear boundary between bleb and sclera.…”
Section: Methodsmentioning
confidence: 99%